2016
DOI: 10.1186/s13065-016-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

A simple and convenient method for the preparation of antioxidant peptides from walnut (Juglans regia L.) protein hydrolysates

Abstract: BackgroundWalnut (Juglans regia L.), that belongs to the Juglandaceae family, is one of the nuts commonly found in Chinese diets. Researchers had obtained peptides from walnut protein hydrolysates, and these peptides exhibited the high antioxidant activities. The objective of this study was to develop a simple and convenient method for a facile and reproducible preparation of antioxidant peptides from walnut protein hydrolysates.ResultsWalnut proteins were extracted from walnut kernels using continuous counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
(50 reference statements)
0
35
0
2
Order By: Relevance
“…Food-derived antioxidant peptides are attracting the interest of research globally because of their safety (Papas, 1999). A number of antioxidant peptides from various animal and plant protein hydrolysates, such as Chinese chestnut protein (Feng, Ruan, Jin, Xu, & Wang, 2018), walnut protein (Liu et al, 2016), pearl millet protein (Agrawal, Joshi, & Gupta, 2016), and monkfish muscle (Chi et al, 2014), have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…Food-derived antioxidant peptides are attracting the interest of research globally because of their safety (Papas, 1999). A number of antioxidant peptides from various animal and plant protein hydrolysates, such as Chinese chestnut protein (Feng, Ruan, Jin, Xu, & Wang, 2018), walnut protein (Liu et al, 2016), pearl millet protein (Agrawal, Joshi, & Gupta, 2016), and monkfish muscle (Chi et al, 2014), have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…The production of fish protein hydrolysates from seafood processing waste via papain, a proteolytic enzyme derived from papaya that has found widespread industrial application, has garnered attention recently because the process is a potential solution for minimizing pollution from fishing industries [39]. Additionally, papain has been researched as a biocatalyst for production of protein hydrosylates from Chinese walnuts; lab-scale work on papain catalysis has shown moderate yields and purities of hydrosylates, and peptides obtained from produced hydrosylates showed good antioxidant properties [40].…”
Section: Food and Beverage Industrymentioning
confidence: 99%
“…The enzymes used for the preparation of WBP must follow the same requirements as other industrial enzymes, which requires not only a wide range of sources, but also a relatively low price. According to the literature, the commonly used walnut proteolytic enzymes are pepsin [19][20][21], trypsin [22,23], alkaline protease [24], papain [25], neutral protease [26], composite protease (pancreatin) [21], etc. As special proteins with physiological activity, enzymes have different activation centers and hydrolysis specificity.…”
Section: Enzymatic Preparationmentioning
confidence: 99%